Long-wavelength pass filter using green CsPbBr3 quantum dots glass. (June 2021) - Zhang, Xizhen; Lin, Mengqi; Guo, Lizhu; Zhang, Yuhang; Cheng, Chuanhui; Sun, Jiashi; Cheng, Yi; Cao, Yongze; Xu, Sai; Li, Xiangping; Zhang, Jinsu; Chen, Baojiu
Highlights: Perovskite quantum dots glasses have been proposed for long-wavelength pass filter. Absorption, luminescence and excitation spectra show exciton absorption and emission. Strong and steep cut-off absorption is determined by first exciton absorption. Long-wavelength pass filters are evaluated for different preparation conditions. Transition wavelength, transmittance, steepness and optical density are provided. Abstract: Perovskite CsPbBr3 quantum dots (QDs) glasses have been investigated for long-wavelength pass filter operating in green light region. The broad absorption band with an absorption shoulder, symmetrical profile of photoluminescence (PL), narrow full width at half maximum (FWHM), broad excitation band, and independence of excitation wavelength show exciton absorption and emission characteristics of semiconductor QDs. Strong cut-off absorption with excellent steepness is determined by first exciton absorption. The long-wavelength pass filter property is evaluated for different preparation conditions. For samples treated at 490, 510, 530 and 550 °C for 3 h, transition wavelength (λtj ) is 494, 511, 518 and 525 nm respectively. Maximum transmittance (Tm) is 84%, 80%, 76% and 64%. Transition region (TR) width is 49, 10, 11 and 58 nm. Optical density (OD) is 2–5 in broad cut-off band. For samples treated at 510 °C for 2 h, 3 h, 5 h and 12 h, the λtj is 511, 511, 513 and 511 nm respectively. The Tm is 76%, 80%, 80% and 76%. The TR width is 14, 10, 16 and 13 nm. The OD is 2–5 in broad cut-off band. The proposed perovskite QDs glass filter is suitable for long-wavelength pass filter application.